River Transport Planning Strategy Analysis Using SWOT and AHP Methods - Yega Mardiansyah; Eva Azhra Latifa (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Tangerang City is the largest city in Banten Province and the third largest city in Greater Jakarta area which is split by one of the major rivers on the island of Java, namely the Cisadane River. With the increasing number of population and vehicle ownership, it is necessary to develop a public transportation network to reduce traffic volume and meet the needs of urban public transportation that is fast, easy, safe and comfortable for the citizen. The existence of the Cisadane River in Tangerang City has the potential to be developed into a public transportation route in the form of a waterway. Therefore, the right strategy is needed in the planning of river transportation. This study aims to analyze the influencing factors and strategic priorities in planning river transportation as urban public transportation using the Strength Weakness Opportunity Threat (SWOT) and Analytical Hierarchy Process (AHP) methods. In this study, a questionnaire was given to eight expert respondents related to river transportation. The respondents' answers were tested for consistency with AHP to ensure the accuracy of the answers. From the results of the SWOT analysis, it was obtained the strengths, weaknesses, opportunities and threats in river transportation planning, as well as the ST (Strength-Threat) strategy with the largest weight of 3.99 as the strategy to be used in planning river transportation. Then from the AHP analysis, the strategic priority results in planning river transportation were obtained, namely the safety criteria with a weight of 0.29 and alternative strategy for life jackets with a weight of 0.117853325 as the main priority in carrying out the chosen strategy. Respondents' answers are fairly accurate with a consistency ratio of 2.58% ≤ 10%.